Power and Negotiation in a University/Community Partnership Serving Jewish Teen Girls - Beth S. Catlett; Amira Proweller; Sonya Crabtree-Nelson (Journal of Community Engagement and Scholarship, 2022)
University/community partnerships involve collaborative work with great potential and risk. This work can allow for productive exchanges that improve the quality of programs and enable broader dissemination of innovative ideas and practices grounded in feminist and social justice ideals. However, institutional demands and individual commitments introduce complications. This paper examines the complex power dynamics that emerge from cross-institutional partnering and program delivery in the context of a feminist education and youth-led participatory action research program for Jewish teen girls. Specifically, we examine the previously under-studied topic of university/community collaboration in which the participating institutions are similarly situated in structures of power. We explore how power dynamics and the partners’ shared and differential strategic goals were negotiated within a context of distinct institutional mandates, with a focus on the pressures of time, funding, and developing youth participatory action research with relatively privileged youth. We discuss implications and strategies for navigating complex university/community engagements that enable balanced, long-term, and sustained partnerships in which mutual interests are served.